UREUM AND CREATININE HEALTH STUDY IN PATIENTS DIABETES MELLITUS - Muhammad Rizki Kurniawan; Eni Kusrini (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2020)
Diabetes mellitus is a metabolic disease that is marked by an increase in blood glucose levels exceeds normal limits. One of the effects of diabetes mellitus is kidney function disorder. Many researches about diabetes mellitus found that patients have uncontrolled levels of urea and creatinine. The purpose of this study was to determine urea and creatinine levels in patients with diabetes mellitus. The research method uses a descriptive approach to determine urea and creatinine levels among diabetes mellitus patients. The results of this study based on the participant characteristics were 47.3% male respondents and 52.7% female respondents, then based on diabetic aged >45 years was 90.95% and <45 years 9.1%. Based on disease duration, illness for five years was 65.5%, 6-10 years 16.3% and >10 years was 18.2%. The overall creatinine and urea levels were normal. The conclusion of this study is a general description of urea and creatinine levels in the study sample within normal limits. However, the age factor of patients less than 45 years and the duration of illness from 6 to 10 years has a risk of increased levels of urea and creatinine in the blood.